2008
DOI: 10.4103/0250-474x.45410
|View full text |Cite
|
Sign up to set email alerts
|

Ionic gelation controlled drug delivery systems for gastric-mucoadhesive microcapsules of captopril

Abstract: A new oral drug delivery system was developed utilizing both the concepts of controlled release and mucoadhesiveness, in order to obtain a unique drug delivery system which could remain in stomach and control the drug release for longer period of time. Captopril microcapsules were prepared with a coat consisting of alginate and a mucoadhesive polymer such as hydroxy propyl methyl cellulose, carbopol 934p, chitosan and cellulose acetate phthalate using emulsification ionic gelation process. The resulting microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This can be explained as due to the reinforcement by CA, which is in line with our previous work (Mooranian et al 2014a). The spectra observed in Figure 2b, d, f and h of chemical analysis showed dominant atoms (Na, O, Ca, S, and Cl) that are expected for a typical PB-SA and PB-CA-SA microcapsule prepared via ionic gelation methodology (Altaf 2008, Davignon, 1994. Na and Cl represent sodium chloride, a by-product of ionic gelation.…”
Section: Swelling Studiesmentioning
confidence: 98%
“…This can be explained as due to the reinforcement by CA, which is in line with our previous work (Mooranian et al 2014a). The spectra observed in Figure 2b, d, f and h of chemical analysis showed dominant atoms (Na, O, Ca, S, and Cl) that are expected for a typical PB-SA and PB-CA-SA microcapsule prepared via ionic gelation methodology (Altaf 2008, Davignon, 1994. Na and Cl represent sodium chloride, a by-product of ionic gelation.…”
Section: Swelling Studiesmentioning
confidence: 98%
“… 69 Nevertheless, nanoparticles produced through this combined approach exhibit excellent physical stability, owing to the role of the added stabilizers during the emulsification process. 80 , 81 Despite its drawbacks, the utilization of both techniques offers a promising strategy for achieving enhanced stability and controlled release properties in drug-loaded nanoparticles.…”
Section: Preparation Methods In Developing Chitosan/alginate-based Na...mentioning
confidence: 99%
“…After the initial dose is delivered by the immediate release layer, the sustained release layer absorbs the gastric fluid and forms a colloidal gel barrier on its surface. This produces a bulk density less than that of the gastric fluid and remains buoyant in the stomach for extended period of time (Altaf et al,2008)Bilayer tablet is shown in Figure 6.…”
Section: Bilayer Tabletmentioning
confidence: 99%